Pilot study: Significance of I-FABP2 in the diagnosis of acute abdominal episodes in children - Szymon Gryboś; Viera Karaffová; Milan Kuchta; Peter Krcho (Elsevier, 2024)
Background: Pediatric abdominal conditions, including necrotizing gastrointestinal diseases, pose significant diagnostic challenges due to clinic symptoms and limited diagnostic tools. Intestinal fatty acid binding protein 2 (I-FABP2) has emerged as a potential biomarker for intestinal damage, but its efficacy in diagnosing pediatric intestinal necrosis remains under explored. Methods: A prospective study was conducted on 55 pediatric patients presenting with abdominal pain and suspected intestinal necrosis or intestinal perforation. Clinical, laboratory, and radiological data were collected, and intraoperative assessment of bowel necrosis was performed. Gene expression of I-FABP2 in peripheral blood was measured using Real-Time RT-PCR, and correlations with surgery and laboratory parameters were analyzed. Results: Intraoperative assessment revealed a moderate sensitivity (61.1%) and specificity (73.7%) of I-FABP2 in identifying bowel necrosis. Positive predictive value (PPV) was high (81.5%), indicating a high likelihood of the condition when I-FABP2 is positive. However, the negative predictive value (NPV) was limited (50%), suggesting challenges in confidently excluding necrosis based on negative I-FABP2 results. Correlations were observed between I-FABP2 expression and elevated levels of C-reactive protein (CRP), interleukin-6 (IL-6), and white blood cell count (WBC), indicating its association with inflammatory processes. Conclusions: While I-FABP2 shows promise as a biomarker for pediatric intestinal necrosis, its diagnostic utility may be enhanced when considered alongside other clinical parameters. Further research and validation studies are warranted to refine its clinical application and improve diagnostic accuracy in pediatric gastrointestinal conditions.